Understanding Philippine History Education in the Age of Disinformation: A Phenomenological Exploration - Amando F. Grata; Raquel F. Llaneta (International Journal of Education and Humanities, 2024)
In Philippine history education, the growing influence of digital media has shifted students' learning preferences, offering both opportunities and challenges. The widespread use of social media platforms like Facebook, YouTube, and TikTok has affected how students access and engage with historical content. A key challenge is that social media, with its easily digestible information, impacts students' attention spans and trust in traditional versus digital sources. This shift underscores the importance of integrating multimedia tools into history education while maintaining rigorous academic standards. This study examines how students' inclination toward social media influences their engagement with historical content and trust in information sources. Using a phenomenological approach, data were collected through in-depth interviews with students from diverse educational backgrounds. The analysis highlights the growing reliance on visual and auditory learning methods, reflecting the "digital native" phenomenon. Although social media offers easy access to information, students still prefer traditionally published historical materials for their credibility and authoritative nature. However, the brevity of social media content tends to reduce students' interest in conducting deeper historical research. The study recommends that educators incorporate multimedia elements in history education to improve student engagement while fostering critical thinking and media literacy. Balancing the use of digital tools with high academic standards is essential to ensure students develop a comprehensive understanding of history